Multiplex RT-PCR for rapid detection of viruses commonly causing diarrhea in pediatric patients - Thongprachum A. (2017)
© 2016 Wiley Periodicals, Inc. Multiplex RT-PCR method using five sets of panel primers was developed for the detection of diarrheal viruses, including rotavirus A, B, and C, adenovirus, astrovirus, norovirus GI and GII, sapovirus, Aichi virus, parechovirus, enterovirus, cosavirus, bocavirus, and Saffold virus. The sensitivity of the method was evaluated and tested with 751 fecal specimens collected from Japanese children with acute diarrhea. Several kinds of viruses were detected in 528 out of 751 (70.3%) fecal specimens. Mixed-infection with different viruses in clinical specimens could also be effectively detected. The method proved to be reliable with highly sensitive and specific and useful for routine diagnosis. J. Med. Virol. 89:818–824, 2017. © 2016 Wiley Periodicals, Inc.